Kewenangan Pemerintah Daerah Dalam Pengawasan Alat Kesehatan - SANDY WIFAQAH (Jurnal Kebijakan Pemerintahan, 2020)
Authority of Local Governments in Supervision of Medical Devices. The phenomenon which is the object of this research is the authority of provincial and district / city regional governments over the supervision of medical devices. The purpose of this study is to discuss the implementation of the authority of the provincial and district / city local governments on the supervision of medical devices. This study uses a normative legal research approach. Data collection techniques using library research. The results of the study are as follows that concurrent government affairs which are the authority of the central government in terms of supervision of medical devices are carried out by the central government by delegating to the governor as the representative of the central government or to vertical institutions in the regions based on the principle of deconcentration; or by assigning regions based on the principle of co-administration. Thus to strengthen Regional Autonomy and to avoid overlapping arrangements, it is necessary to have clear and firm mechanisms of guidance, supervision, empowerment, and sanctions. The existence of coaching and supervision as well as clear and clear sanctions requires clarity of guidance, supervision from the Ministry that conducts general guidance and supervision as well as ministries / non-ministerial government agencies that carry out technical guidance. For this reason, synergy between the Central and Regional Governments, ministries / non-ministerial government institutions/ institutions is needed to make Norms, Standards, Procedures And Criteria (NSPK) to be used as a guideline for regions in carrying out Government Affairs which are submitted to the regions and become guidelines for government ministries/ institutions. non-ministry to provide guidance and supervision. Keywords: Local Government, Oversight of Medical Devices, and Regional Autonomy.